What you need to know when you can't find your UNIX system administrator - Mui, Linda (O'Reilly, 1995)
If you\'re like most UNIX users, you have a job to do aside from exploring your operating system -- like analyzing that hot new stock, running another experiment, or typesetting another report. What happens when you have problems? What happens when the system slows to a crawl, when you can\'t get logged back in after a power failure, or when you\'ve sent a file to the printer three times but have yet to find a printout? When You Can\'t Find Your UNIX System Administrator, part of our new What You Need to Know series, gives you tools for solving problems. It offers: Practical solutions for problems you\'re likely to encounter in logging in, running programs, sharing files, managing space resources, printing, and so on Just enough background so that you can make sense of our suggestions, rather than simply memorizing keystrokes An explanation of how to present problems to your sys admin so that you\'re more likely to get quick, accurate support A list of the site-specific information to which you should have access, and a place to write it down A quick-ref card summarizing what to try first, second, third for commonly encountered problems The goal of this book is not to make you a guru, but to get you back to the job you\'d rather be doing.
Keywords: technika; knihovnictví, informační věda a muzeologie; počítačové systémy; unix; lékařská informatika; Computer Systems